Recommendation for a World Virtual School Project - Sorić, Neven (Array, 2009)
World Virtual School (WVS) is a project sponsored by the U.S. Department of State Office of Overseas Schools. It has gathered eight representatives from eight major international school regions to form a WVS Advisory Group. The group’s objective is to conduct research in virtual learning environments (VLE) of overseas schools, to analyze and present the results in order to offer a WVS structure plan. The goal is to increase the usage of VLE systems throughout the world to make this project global having in mind its relevancy, accessibility, durability and affordability. Therefore, we bring a possible WVS project outcome, recommending a shared global VLE.